EMOTIONAL UNPREPAREDNESS AND MARRIAGE POSTPONEMENT AMONG MUSLIMS: A MASLAHAH MURSALAH ANALYSIS OF WAITHOOD IN PALU CITY - Az-Zahra, Hanifa; Salsabila, Nur Saifa; Rahmawati; Ikhlas; Rahmatullah, Nursalam (Program Studi Perbandingan Mazhab, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2025)
This study examines marriage postponement (waithood) among Muslims in Palu City through the lens of maslahah mursalah in Islamic jurisprudence, addressing the limited attention given to emotional readiness within existing studies on waithood. Employing a qualitative descriptive design with an empirical juridical and normative theological approach, data were collected through interviews, observation, and documentation involving eight Muslim individuals who delayed marriage due to emotional unpreparedness. The findings identify four dominant psychological and social factors underlying marriage postponement: past trauma, fear of marital failure, family responsibilities, and concerns over post-marital socio-economic stability. Drawing on Imam al-Ghazali’s framework of maslahah mursalah, this study argues that postponing marriage to attain emotional readiness constitutes a form of preventive public interest (maslahah wiqā’iyyah), as it serves the objectives of Islamic law (maqāṣid al-sharīʿah), particularly the preservation of psychological well-being (ḥifẓ al-nafs), rational deliberation (ḥifẓ al-ʿaql), and family continuity (ḥifẓ al-nasl). This research contributes to Islamic family law discourse by reframing waithood as an ethically grounded and legally coherent strategy rather than a deviation from Islamic norms, thereby extending waithood studies into the psychological–emotional dimension within an Islamic legal framework.